Differential neural response to psychoanalytic intervention techniques during structural interviewing: A single-case analysis using EEG - Buchheim, Anna; Kernberg, Otto F.; Netzer, Nikolaus; Buchheim, Peter; Perchtold-Stefan, Corinna; Sperner-Unterweger, Barbara; Beckenbauer, Fabian; Labek, Karin (Frontiers in Human Neuroscience, 2023)
Background: Previous studies have detected changes in the EEG signal as an effect of psychoanalytic interventions. However, no study has as yet investigated neural correlates of specific psychoanalytic interventions in the EEG power spectrum. In the present case study, we contrasted three types of interventions (clarification, confrontation, interpretation) and a neutral control condition during a structural psychoanalytic interview conducted while EEG was recorded. Methods: A 27-year-old male patient diagnosed with major depressive disorder and borderline personality disorder with recurrent suicidal and self-injurious behavior underwent a structural interview while recording EEG. Two independent experts selected by consensus the characteristic episodes of the four conditions (clarification, confrontation, interpretation, neutral control) within the interview which were included in the EEG analyses. Fast Fourier transformation (FFT) was applied to subsegments of the intervention type to analyze the EEG power spectra. Alpha and beta power from central, frontal and parietal sites were considered in linear mixed effects models with segments as a random factor with maximum-likelihood estimates due to the lack of balance in the length of the interview segments. Results: The interventions “interpretation” and “confrontation” showed a significantly lower alpha power compared to the control condition in central electrodes. In the frontal and parietal sites of the alpha power and in all beta power sites, the omnibus tests (full model/model without intervention) and comparisons relative to control conditions showed a no significant overall result or failed significance after alpha error correction. Conclusion: Incisive interventions such as confrontation with discrepancies and interpretation of unconscious intrapsychic conflicts may have provoked temporary emotional lability leading to a change in psychic processing akin to interference from external stimuli. This conclusion is consistent with the finding that interpretations, which are potentially the most concise interventions, had the strongest effects on alpha power. Using EEG during therapeutic psychoanalytic intervention techniques might be a helpful tool to evaluate differential responses to the psychotherapeutic process on a neural level. However, this single case result has to be replicated in a larger sample and does not allow generalizations.